2011
DOI: 10.1111/j.1432-2277.2011.01314.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA-G on peripheral blood CD4+ T lymphocytes: a potential predictor for acute renal rejection

Abstract: Summary HLA‐G Expression in grafts and serum has been shown to improve graft acceptance. However, its expression on peripheral blood lymphocytes (PBLs) during acute rejection (AR) remains unknown. In this study, we serially monitored HLA‐G expression on CD4+ and CD8+ PBLs of 66 recipients undergoing renal transplantation using flow cytometry at different time points before and after transplantation, as well as during AR episode. In stable recipients, HLA‐G expression on CD4+ PBLs declined during the first week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…It was shown that HLA‐G + CD4 + T cells and the expression level of HLA‐G on CD4 + T cells were significantly decreased after acute rejection. It is worthwhile to note that when acute rejection occurred, HLA‐G levels decreased compared with before and during the follow‐up phase after acute rejection (N. Lu et al, ). Other study reported that high‐level sHLA‐G after transplantation was independently related to graft acceptance.…”
Section: Adaptive Immunity In Kidney Transplantation Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that HLA‐G + CD4 + T cells and the expression level of HLA‐G on CD4 + T cells were significantly decreased after acute rejection. It is worthwhile to note that when acute rejection occurred, HLA‐G levels decreased compared with before and during the follow‐up phase after acute rejection (N. Lu et al, ). Other study reported that high‐level sHLA‐G after transplantation was independently related to graft acceptance.…”
Section: Adaptive Immunity In Kidney Transplantation Outcomementioning
confidence: 99%
“…Kidney graft is immediately damaged by the immune response during graft rejection, which is considered as the major cause of graft loss (J. Lu & Zhang, 2016;N. Lu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown a significant increase in proportions of HLA-G+ CD4+ T cells post-renal transplantation in patients with stable graft function [39]. Furthermore, these cells were able to suppress a mixed lymphocyte reaction, indicative of a contribution to graft survival [40]. HLA-G expressed by dendritic cells or in soluble form can downregulate CD4 and CD8 on allostimulated T cells, leading to generation of suppressor function [41].…”
Section: Discussionmentioning
confidence: 95%
“…In the context of kidney transplants, it has been reported that HLA-G expression on T cells increases after the transplant, but significantly decreases in subjects experiencing an acute rejection. This data suggests that HLA-G might be involved in the protection of transplants against rejection and the levels of HLA-G on CD4+ may represent a potential marker in predicting episodes of renal rejection after kidney transplantation ( 58 , 59 ).…”
Section: Hla-g-expressing Immune Cells In Non-autoimmune Diseasesmentioning
confidence: 89%